Effect of asymmetric diffuser deflector on even distribution of steam leaving blade section of steam turbine: comparative computational study - Bobčík, Marek; Pospíšil, Jiří; Fiedler, Jan (Case studies in thermal engineering, 2025)
This study presents a computational analysis comparing two designs of steam turbine diffuser deflectors: a conventional axisymmetric design and an innovative asymmetric design. The computational comparison is carried out for a real turbine with a power output of 1.090 MW. Utilizing ANSYS CFX simulations based on the finite volume method, the innovative deflector demonstrates extending the steam expansion, which is directly related to the up to 5 % increase in the output power of the turbine last stage blades. The asymmetric steam turbine diffuser deflector geometry promotes a more uniform static pressure distribution and reduces flow separation and recirculation zones, leading to decreased pressure losses between the turbine's inner and outer casings.